(untitled) (The Journal of Forensic Accounting Profession, 2022)
Fraud in accounting, as well as falsification of financial statements, has a long history, and in recent years their scale has been growing and with much more serious consequences. Decisions made by investors and other users of financial statements based on erroneous financial information cause enormous damage to users of financial information, but also to the general public. Many major financial frauds are only detected when companies reach the point of financial collapse, in a situation where it is difficult to do something to repair major damages. (Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2022-0001, pod licencom CC BY-NC-ND 4.0)